2016
DOI: 10.19173/irrodl.v17i3.2426
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Tensions in the Use of Open Licenses in OER Repositories

Abstract: We present an analysis of 50 repositories for educational content conducted through an "audit system" that helped us classify these repositories, their software systems, promoters, and how they communicated their licensing practices. We randomly accessed five resources from each repository to investigate the alignment of licensing information between the resources themselves, metadata pages and overall site policies. We identified a high level of incongruity that could lead to a limited impact in OER use and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 7 publications
2
5
0
1
Order By: Relevance
“…However, in a significant number of ROERs (14.5%), the platform was not identified, as it was not mentioned in their policies or anywhere else. This result coincides with that of OpenDOAR and Bueno-de-la-Fuente (2009), although recent studies (Amiel & Soares, 2016) have indicated a tendency to adopt CMS in the ROER scene. Table 9 Software Platform Metadata standards.…”
Section: Geographical Originsupporting
confidence: 89%
See 1 more Smart Citation
“…However, in a significant number of ROERs (14.5%), the platform was not identified, as it was not mentioned in their policies or anywhere else. This result coincides with that of OpenDOAR and Bueno-de-la-Fuente (2009), although recent studies (Amiel & Soares, 2016) have indicated a tendency to adopt CMS in the ROER scene. Table 9 Software Platform Metadata standards.…”
Section: Geographical Originsupporting
confidence: 89%
“…In some studies, 76% of ROER had copyright policies (Tzikopoulos et al, 2007) and 52.5% (Atenas & Havemann, 2013) or 22% (Amiel & Soares, 2016) had CC licenses. Our results were more positive, since they showed an increase in openness of ROER and in the use of CC.…”
Section: Table 14mentioning
confidence: 99%
“…The possibility for learning and teaching to be repositioned as a social commons that facilitates the public good rather than as intellectual property in a competitive marketplace (Amiel and Soares 2016) has been enhanced by the widening availability of digital technologies that facilitate the exchange of ideas within and beyond the boundaries of formal educational spaces, although this represents a new iteration in the history of educational openness rather than a complete break from the past (Peter and Deimann 2015). However, the fact that this narrative is now frequently experienced as counter-traditional is perhaps why OE is frequently understood as a revolutionary social movement rather than simply a pedagogic or technical strategy.…”
Section: Oep As Troublesomementioning
confidence: 99%
“…Cohen, Omolla, and Malick (2014) While the aforementioned research looked at the architecture of OER platforms in individual contexts, only one study examined the use of OER platforms across multiple contexts. Amiel and Soares (2016) conducted a survey of OER leaders in Latin America countries, asking them what the most important OER repositories were in their country. Once repository information had been collected, the authors did a content analysis of the repositories to examine the infrastructure used for the repository and how well licensing information was displayed within the repository.…”
Section: Oer and Platformsmentioning
confidence: 99%
“…Albeit limited in scope, Amiel and Soares' (2016) research nonetheless represents an important effort in critically examining the technology that institutions are using to deliver OER. Importantly, their research points out misalignment between the goals of OER (as easy to find and use) and technology used to deliver it.…”
Section: Oer and Platformsmentioning
confidence: 99%